Potential and Management of Juvenil Payangka fish Ophieleotris aporos in lake Tondano - Jan W F S Tamanampo; Nego E. Bataragoa (Jurnal Ilmiah PLATAX, 2017)
At this time, the nike fish in Tondano Lake has been exploited intensively in the great times.  The results show that the number of nike fishing fleets operating every  night during August 2017 fluctuated from 41 to 234 with an average of 108 fleet catchers. . Nike fish catches each month from 108 catchers are 1.2773 tonwith an individual number of 61.705.314.337,  If effectively the fisherman operate 11 month then the production of nike fish used by fisherman is 14.047 ton/year.            Fish payangka spawn throughout the year in declared with the the maturity level found gonado IV (ready to spawn phase).  The Gonad Maturity Index (GMI or IKG) shows the spawning peak in July 2017 (2.85 %  ale and Female 6.57 % and August 2017 (3.16 % male and 3.31 %).  Fecundity (number of eggs) on average each month varies based on time and location are 12.409 – 60.591 grain with an overall average of 25.613 grains.Keywords: Potential, juvenile fish, IKG, and Fecundity   AbstrakPada saat ini ikan nike  di danau Tondano telah dieksploitasi secara intensif dalam kala besar. Hasil pencatatan menunjukkan bahwa jumlah armada penangkap ikan nike yang beroperasi setiap malam sepanjang bulan Agustus 2017 berfluktuasi dari  41 sampai 234  dengan rata-rata 108 armada penangkap. Hasil tangkapan ikan nike setiap bulan dari  108  alat penangkap  adalah 1.2773 Ton, dengan jumlah individu sebanyak 61.705.314.337 . Bila secara efektif nelayan beroperasi 11 bulan maka produksi ikan nike yang dimanfaatkan nelayan sebesar 14.047 Ton / Tahun.Ikan Payangka memijah sepanjang tahun di nyatakan dengan ditemukan Tingkat Kematangan Gonad IV ( fase siap memijah). Indeks Kematangan Gonad (IKG) memperlihatkan puncak pemijahan  di  Juli 2017 (IKG Jantan 2.85 % dan betina 6.57 %) dan Agustus 2017 ( IKG Jantan 3.16 % dan betina 8.31 %).  Fekunditas (jumlah telur) rata-rata setiap bulan bervariasi berdasarakan waktu dan lokasi yakni 12.409 – 60.591 butir dengan rata-rata keseluruhan 26.613 butir.Kata kunci: Potensi, juvenile ikan, IKG,dan  Fekunditas